HPA Axis Gene Expression and DNA Methylation Profiles in Rats Exposed to Early Life Stress, Adult Voluntary Ethanol Drinking and Single Housing - Todkar, Aniruddha; Granholm, Linnea; Aljumah, Mujtaba; Nilsson, Kent W.; Comasco, Erika; Nylander, Ingrid (Frontiers in Molecular Neuroscience, 2016)
The neurobiological basis of early life stress (ELS) impact on vulnerability to alcohol use disorder is not fully understood. The effect of ELS, adult ethanol consumption and single housing, on expression of stress and DNA methylation regulatory genes as well as blood corticosterone levels was investigated in the hypothalamus and pituitary of adult out-bred Wistar rats subjected to different rearing conditions. A prolonged maternal separation of 360 min (MS360) was used to study the effect of ELS, and a short maternal separation of 15 min (MS15) was used as a control. Voluntary ethanol drinking was assessed using a two-bottle free choice paradigm to simulate human episodic drinking. The effects of single housing and ethanol were assessed in conventional animal facility rearing (AFR) conditions. Single housing in adulthood was associated with lower Crhr1 and higher Pomc expression in the pituitary, whereas ethanol drinking was associated with higher expression of Crh in the hypothalamus and Crhr1 in the pituitary, accompanied by lower corticosterone levels. As compared to controls with similar early life handling, rats exposed to ELS displayed lower expression of Pomc in the hypothalamus, and higher Dnmt1 expression in the pituitary. Voluntary ethanol drinking resulted in lower Fkbp5 expression in the pituitary and higher Crh expression in the hypothalamus, independently of rearing conditions. In rats exposed to ELS, water and ethanol drinking was associated with higher and lower corticosterone levels, respectively,. The use of conventionally reared rats as control group yielded more significant results than the use of rats exposed to short maternal separation. Positive correlations, restricted to the hypothalamus and ELS group, were observed between the expression of the HPA receptor and the methylation-related genes. Promoter DNA methylation and expression of respective genes did not correlate suggesting that other loci are involved in transcriptional regulation. Concluding, single housing is a confounding factor to be considered in voluntary ethanol drinking paradigms. ELS and ethanol drinking in adulthood exert independent effects on hypothalamic and pituitary related genes, however in a manner dependent on the control group used.